Assessment of acetylcholinesterase activity in CD9-positive exosomes from patients with Parkinson’s disease - Jeong, Sumin; Shim, Kyu Hwan; Kim, Danyeong; Bae, Heewon; Jeong, Da-Eun; Kang, Min Ju; An, Seong Soo A. (Frontiers in Aging Neuroscience, 2024)
Introduction Parkinson’s disease (PD) is a neurodegenerative disorder characterized by dopaminergic dysfunction and associated with abnormalities in the cholinergic system. However, the relationship between PD and cholinergic dysfunction, particularly in exosomes, is not fully understood. Methods We enrolled 37 patients with PD and 44 healthy controls (HC) to investigate acetylcholinesterase (AChE) activity in CD9-positive and L1CAM-positive exosomes. Exosomes were isolated from plasma using antibody-coupled magnetic beads, and their sizes and concentrations were assessed using transmission electron microscopy, nanoparticle tracking analysis, and western blotting. Subsequently, the AChE activity in these exosomes was analyzed in relation to various clinical parameters. Results A significant decrease in AChE activity was observed in CD9-positive exosomes derived from patients with PD, whereas no significant differences were found in L1CAM-positive exosomes. Further analysis with a larger sample size confirmed a substantial reduction in AChE activity in CD9-positive exosomes from the PD plasma, with moderate diagnostic accuracy. The decrease in AChE activity of CD9-positive exosomes did not show an association with cognitive impairment but displayed a trend toward correlation with PD progression. Discussion The reduction in AChE activity in CD9-positive exosomes suggests potential peripheral cholinergic dysfunction in PD, independent of the central cholinergic system. The observed alterations in AChE activity provide valuable insights into the association between cholinergic dysfunction and the pathogenesis of PD.